The lincoln lawyer ebook - Connelly, Michael (Lincoln Lawyer, 2005)
INSPIRATION FOR THE ORIGINAL SERIES THE LINCOLN LAWYER – THE #1 TV SHOW ON NETFLIX The bestselling legal thriller has charismatic defense attorney Mickey Haller taking on a slam-dunk court case involving a Beverly Hills playboy — but as it spirals into a nightmare, he finds himself in a fight for his life.   Mickey Haller is a Lincoln Lawyer, a criminal defense attorney who operates out of the backseat of his Lincoln Town Car, traveling between the far-flung courthouses of Los Angeles to defend clients of every kind. Bikers, con artists, drunk drivers, drug dealers — they're all on Mickey Haller's client list. For him, the law is rarely about guilt or innocence, it's about negotiation and manipulation. Sometimes it's even about justice.   A Beverly Hills playboy arrested for attacking a woman he picked up in a bar chooses Haller to defend him, and Mickey has his first high-paying client in years. It is a defense attorney's dream, what they call a franchise case. And as the evidence stacks up, Haller comes to believe this may be the easiest case of his career. Then someone close to him is murdered and Haller discovers that his search for innocence has brought him face-to-face with evil as pure as a flame. To escape without being burned, he must deploy every tactic, feint, and instinct in his arsenal — this time to save his own life.